2019
DOI: 10.1002/cctc.201900178
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Transition Metal Co‐Doped Ceria Catalysts for Low‐Temperature CO Oxidation

Abstract: We present a highly active CeO 2 -based catalyst for oxidizing CO in automobile exhaust. This catalyst was systemically designed by co-doping with transition metals (TMs). First, we used density functional theory (DFT) calculations to screen Mn and 13 dopant TMs (periods 4~6 in groups VIII~XI) and their 91 binary combinations for co-doping. As a result, Cu and (Cu, Ag) were found to be the best candidates among the single and binary dopants, respectively. Next, we synthesized CeO 2 nano-particles doped with Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 69 publications
6
32
0
Order By: Relevance
“…reported that TM‐co‐doped CeO 2 catalyst had a critical effect on catalytic activity . Our group performed theoretical analysis of these results and reported a linear correlation between E vf and catalytic activity in co‐doping as well as in single‐metal doping . In addition, it is very important to select co‐doping combination candidates because the catalytic activity differs depending on the co‐dopant, as confirmed by Park et al…”
Section: Improving Co Oxidation By Enhancing the Intrinsic Activity Omentioning
confidence: 76%
See 4 more Smart Citations
“…reported that TM‐co‐doped CeO 2 catalyst had a critical effect on catalytic activity . Our group performed theoretical analysis of these results and reported a linear correlation between E vf and catalytic activity in co‐doping as well as in single‐metal doping . In addition, it is very important to select co‐doping combination candidates because the catalytic activity differs depending on the co‐dopant, as confirmed by Park et al…”
Section: Improving Co Oxidation By Enhancing the Intrinsic Activity Omentioning
confidence: 76%
“…In this sense, the energy required to detach a lattice oxygen atom from the surface, that is oxygen vacancy formation energy ( E vf ), can be considered as a feasible descriptor to describe the activity of CO oxidation. In many previous studies, the E vf showed inverse correlation with the measured catalytic activity of CO oxidation on doped or undoped CeO 2 (111), suggesting that lower E vf of a CeO 2 ‐based catalyst enhanced its activity . Therefore, E vf can be used to effectively predict the activity of CeO 2 ‐based catalysts in CO oxidation.…”
Section: Improving Co Oxidation By Enhancing the Intrinsic Activity Omentioning
confidence: 92%
See 3 more Smart Citations